Acarboxyprothrombin concentration [corrected] after oral prophylactic vitamin K. Issue 9 (September 1987) - von Kries, R; Kreppel, S; Becker, A; Tangermann, R; Göbel, U
Abstract : The effect of prophylaxis with oral vitamin K (1 mg vitamin K1 given with the first feed) on the rate of detection of acarboxyprothrombin (PIVKA II) and factor II clotting concentration [corrected] were analysed. Introducing such prophylaxis reduced the rates of detection of PIVKA II concentration [corrected] on day 5 from 48% to zero. None of the babies given prophylaxis had factor II clotting concentration [corrected] below 40%, compared with 34 of 95 babies not given prophylaxis. This study has important implications in the prophylaxis of both classical and late onset haemorrhagic disease of the newborn.